State-selective Rydberg excitation with femtosecond pulses - Kozák, M. (2013)
We show that multipulse excitation of Rydberg atoms with a sequence of short time-delayed femtosecond pulses results in strong n selection of the final-state amplitudes. In the experiment, a 150 fs laser pulse, which alone populates n levels from 22–32 in Li, is chopped into four time-delayed excitation pulses, which results in a strong modification of the n-level distribution. The mechanism demonstrated in the experiment is derived theoretically: With more pulses, it is shown that the population of a single or a few n levels can be performed on demand and varied as long as the central laser frequency is given.